A micro-spreading improvement for spermatogenic chromosomes from Triatominae (Hemiptera-Reduviidae) (2006)
ABSTRACT: Cytogenetics of triatomines have been a valuable biological tool for the study of evolution, taxonomy, and epidemiology of these vectors of Trypanosoma cruzi. Here we present a single microtube protocol that combines micro-centrifugation and micro-spreading, allowing high quality cytogenetic preparations from male gonadal material of Rhodnius prolixus and Triatoma lecticularia. The amount of cellular scattering can be modulated, which can be useful if small aggregates of synchronous cells are desired. Moreover, a higher number of slides per gonad can be obtained with fully flattened clean chromosomal spreads with minimum overlaps, optimal for classical and modern molecular cytogenetic analyses.